2012
DOI: 10.1002/em.21729
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐PKcs‐dependent NHEJ pathway supports the progression of topoisomerase II poison‐induced chromosome aberrant cells

Abstract: The role of DNA double strand break (DSB) repair pathways, non-homologous end joining (NHEJ), and homologous recombination (HR) was evaluated to prevent the chromosome instability induced by the topoisomerase II (Top2) poisons, idarubicin, and etoposide in Chinese hamster cell lines. XR-C1 (DNA-PKcs deficient) and V-C8 (BRCA2 deficient) showed higher sensitivity to increased concentrations of Top2 poisons compared with their normal counterparts, CHO9 and V79. Both proficient and deficient cells exhibited a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…Nonhomologous end-joining is the predominant mechanism of DSB repair in eukaryotes and is often prone to error, which might lead to the amplification or loss of chromosomal material. At the late stage of DSB repair processes, if, for example, the deleted chromosomal regions remain in the cytoplasm, these events are likely to lead to MN formation . In this study, slight induction of MN formation by PFOS was observed in the bone marrow of gpt delta transgenic mice, which was consistent with previous observations in rats …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonhomologous end-joining is the predominant mechanism of DSB repair in eukaryotes and is often prone to error, which might lead to the amplification or loss of chromosomal material. At the late stage of DSB repair processes, if, for example, the deleted chromosomal regions remain in the cytoplasm, these events are likely to lead to MN formation . In this study, slight induction of MN formation by PFOS was observed in the bone marrow of gpt delta transgenic mice, which was consistent with previous observations in rats …”
Section: Discussionsupporting
confidence: 92%
“…At the late stage of DSB repair processes, if, for example, the deleted chromosomal regions remain in the cytoplasm, these events are likely to lead to MN formation. 36 In this study, slight induction of MN formation by PFOS was observed in the bone marrow of gpt delta transgenic mice, which was consistent with previous observations in rats. 37 It has been reported that the mutagenic potential PFOS was negative in S. typhimurium stains by bacterial reverse mutation assay (Ames test).…”
Section: Environmental Science and Technologysupporting
confidence: 93%
“…Moreover, our previous results have shown that D-NHEJ allows Chinese hamster cells that were treated with Top2 poisons during S/G2 to progress into the following interphase (Elguero et al 2012). Here, we evaluated the role of potentially error-prone D-NHEJ and B-NHEJ repair pathways in the conversion of persistent DNA damage to chromosomal rearrangements following ETO treatment in G2 phase, since these pathways may be associated with cancer development.…”
Section: Introductionmentioning
confidence: 99%